The karma of consumption: Role of materialism in the pursuit of life satisfaction - Roy, Rajat; Rabbanee, Fazlul; Chaudhuri, Himadri R; Menon, Preetha (Emerald, 2020)
Purpose: This paper aims to examine how social comparison (SC) and belief in karma (KA) encourage materialism (MAT) and promote consumers’ life satisfaction (LS).